A terceira idade e a Internet: uma questão para o novo milênio - Dominguez Garcia, Heliéte [UNESP] (Universidade Estadual Paulista (Unesp), 2001)
With the beginning of the new millennium, the Brazilian society is being transformed. It is believed that, by the year 2025, one in five Brazilian citizens will be 60 years old. The youngsters are prepared to deal with new technologies but the previous generations, which are currently considered to be the elderly, are not. In fact, they live in a society which is highly technological. Based on these facts, the purposes of this research are: to characterize the potential elderly user as for the use of the Internet in UNATI - UEL and SENAC - Londrina groups; to identify the use of the Internet by the elderly; to verify if the elderly are familiarized with the Internet and to detect their feelings and aspirations towards the Internet. The methodology used in this research was the case study under a qualitative-quantitative focus. A different questionnaire with open-ended and multiple choice questions was used for each institution studied in this research. The results obtained led us to the following conclusions: 1) both groups understand the importance of the use of the Internet nowadays; 2) it is easier and more comfortable for them to accomplish their daily tasks with the Internet; 3) the Internet brings information and stimulates creativity.

Com o início do novo milênio, o Brasil passa por profundas transformações na sociedade. Estima-se que, em 2025, a cada cinco brasileiros um terá 60 anos. Os jovens de hoje estão preparados para lidarem com as novas tecnologias. No entanto, as gerações anteriores, consideradas atualmente da Terceira Idade, não tiveram esta formação e estão vivendo numa sociedade altamente informatizada. Esta pesquisa tem como objetivos: Caracterizar o usuário potencial da Terceira Idade, quanto ao uso da Internet nos grupos da UNATI-UEL e do SENAC-Londrina; Identificar a utilização da Internet por usuários da Terceira Idade; Verificar se a Terceira Idade está familiarizada com a Internet e Detectar os sentimentos e aspirações dos usuários da Terceira Idade diante da Internet. A metodologia utilizada nesta pesquisa foi de estudo de caso, sob um enfoque quantitativo-qualitativo. Utilizamos questionário com perguntas abertas e fechadas, diferentes para cada instituição estudada. Os resultados obtidos nos permitem concluir que: 1) ambos os grupos pesquisados compreendem a importância da utilização da Internet nos dias de hoje; 2) esta oferece maior facilidade e comodidade na realização de suas tarefas diárias; 3) traz informação e estimula a criatividade.
Keywords: Idosos; Internet; Redes de computadores; Terceira Idade; Elderly; Senior citizen; Internet